Laparoscopic gastric devascularization without splenectomy is effective for the treatment of gastric varices. (2016) - Zuiki, Toru; Hosoya, Yoshinori; Sakuma, Yasunaru; Hyodo, Masanobu; Lefor, Alan T.; Sata, Naohiro; Nagamine, Nobuhiko; Isoda, Norio; Sugano, Kentaro; Yasuda, Yoshikazu
Highlights: Devascularization without splenectomy for gastric varices reduces the complication. Laparoscopic devascularization without splenectomy is effective and less invasive. Further improvement of laparoscopic devices will enhance the safety operation. The new preoperative criteria to predict the difficulty of surgery is required. Abstract: Introduction: Laparoscopic gastric devascularization of the upper stomach in patients with gastric varices has rarely been reported. Perioperative clinical data were compared with patients who underwent open surgery. Presentation of cases: From 2009 to 2012, we performed laparoscopic gastric devascularization without splenectomy for the treatment of gastric varices in eight patients. The patients included four males and four females. Peri-gastric vessels were divided using electrical coagulating devices or other devices according to the diameter of the vessels. Two patients underwent conversion to open surgery due to intraoperative bleeding. Discussion: Intraoperative blood loss in patients who accomplished laparoscopic devascularization was very small (mean 76 ml). However, once bleeding occurs, there is a risk of causing massive bleeding. Conclusion: With further improvement of laparoscopic devices, laparoscopic gastric devascularization without splenectomy must be an effective and less-invasive surgical procedure in the treatment of gastric varices.